8‐Prenylflavanones through Microwave Promoted Tandem Claisen Rearrangement/6‐endo‐trig Cyclization and Cross Metathesis. Issue 47 (16th November 2020) - Schultze, Christiane; Foß, Stefan; Schmidt, Bernd
Abstract : Prenylated flavanones were obtained from ortho ‐allyloxy chalcones through a one‐pot sequence of Claisen rearrangement and 6‐ endo ‐trig cyclization, followed by olefin cross metathesis of the intermediate allyl flavanones with 2‐methyl‐2‐butene. The synthetic utility of this route is illustrated for the synthesis of several naturally occurring prenyl flavanones. Abstract : Microwave irradiation of ortho ‐allyloxy chalcones promotes a tandem sequence of Claisen rearrangement and 6‐ endo ‐trig‐cyclization. Olefin cross metathesis then furnishes prenylated flavonoids. The method has, inter alia, been applied to the synthesis of an angular chromene‐annellated natural product and its linear isomer. Both occur in medicinal plants indigenous in India and Nigeria respectively.